2023
DOI: 10.3390/ijms24108850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Therapeutic Hypothermia on Macrophages in Mouse Cochlea Explants

Abstract: Globally, over the next few decades, more than 2.5 billion people will suffer from hearing impairment, including profound hearing loss, and millions could potentially benefit from a cochlea implant. To date, several studies have focused on tissue trauma caused by cochlea implantation. The direct immune reaction in the inner ear after an implantation has not been well studied. Recently, therapeutic hypothermia has been found to positively influence the inflammatory reaction caused by electrode insertion trauma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although these studies showed benefits of MTH, systemic application can result in unintended complications and is simply not feasible as a therapeutic application for a global population. Recent studies in cochlear implant trauma ( Tamames et al, 2016 ; Bader et al, 2023 ; Schmutzhard et al, 2023 ) and cisplatin injury ( Spankovich et al, 2016 ; Stanford et al, 2020 ) models provide evidence for localized MTH providing cochlear neuroprotection. Furthermore, several approaches have been proposed to achieve therapeutic levels of hypothermia ( Spankovich et al, 2016 ; Tamames et al, 2016 , 2018 ; Bader et al, 2020 ; Stanford et al, 2020 ; Arteaga et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies showed benefits of MTH, systemic application can result in unintended complications and is simply not feasible as a therapeutic application for a global population. Recent studies in cochlear implant trauma ( Tamames et al, 2016 ; Bader et al, 2023 ; Schmutzhard et al, 2023 ) and cisplatin injury ( Spankovich et al, 2016 ; Stanford et al, 2020 ) models provide evidence for localized MTH providing cochlear neuroprotection. Furthermore, several approaches have been proposed to achieve therapeutic levels of hypothermia ( Spankovich et al, 2016 ; Tamames et al, 2016 , 2018 ; Bader et al, 2020 ; Stanford et al, 2020 ; Arteaga et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%